Polityczno-prawne uwarunkowania rozwoju bezpośredniej sprzedaży produktów rolniczych - Dziedzic, Sylwia (Political and legal conditions for development of direct sales of agriculture products, 2006)
The article presents some political and legal conditions for the development of direct sales of agriculture products. To this aim the PEST analysis was conducted on the basis of expert method and the achieved results were presented.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1137, s. 47-56